2017
DOI: 10.1002/slct.201702077
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Reusable Metal Heterogeneous Catalysts for Conversion of CO2Prepared from a Microwave Synthetized Porous Polyiminopyridine

Abstract: A stable nitrogen‐rich porous polyimine containing pyridine units (PIPy‐4Mw) was successfully synthesized under microwave heating via a simple “one‐step” polycondensation in only 30 min without adding any catalyst. This versatile polymer can incorporate different transition metals leading polyiminopyridine‐supported catalysts; in this paper we report the synthesis and catalytic performance of heterogenized complexes of abundant earth metals such as iron(II), cobalt(II) and chromium(III) (PIPy‐4MwFe, PIPy‐4MwCo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 35 publications
(34 reference statements)
7
12
0
Order By: Relevance
“…The decomposition temperature of the metal supported poly(azomethine‐pyridine)s was around 380 °C (Fig. ), lower than the corresponding starting support as it was previously reported for metal‐containing polymers …”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…The decomposition temperature of the metal supported poly(azomethine‐pyridine)s was around 380 °C (Fig. ), lower than the corresponding starting support as it was previously reported for metal‐containing polymers …”
Section: Resultsmentioning
confidence: 63%
“…Recently, we have reported that CO 2 can be converted into cyclic carbonates using metal porous polymers at relatively mild conditions: 7 atm of CO 2 , 100 °C, without solvent, with relationships epoxide/metal of 1500 and in the presence of a base as dimethylaminopyridine (DMAP), which improve the activity of the catalysts generating more electron‐rich centers in the metal . Following this protocol and styrene oxide as substrate model, we found that all supported metal–poly(azomethine‐pyridine)s (Table , Entries 1–4) result very effective catalysts with high conversions, between 91% and 98%, and with the formation of cyclic carbonate as unique product (see 1 H‐NMR spectrum in Supporting Information, Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, iron could be considered as the optimum choice from a sustainable approach because it is cheap, earth abundant, and has relatively low toxicity [ 8 ]. Thus, in the last few years, some heterogeneous iron catalysts, that effectively promote this reaction, have been reported, e.g., iron doped mesoporous zeolites [ 9 , 10 ], a porous covalent triazine-based polymer containing iron oxide nanoparticles [ 11 ] and some iron-based poly(azomethine)s [ 12 , 13 , 14 ]. All reactions carried out with iron-containing heterogeneous catalysts produced cyclic carbonates in high yields, using CO 2 pressures between 3 and 20 bar and reaction temperatures in the range of 50–120 °C [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%